Effect and Removal Mechanisms of 6 Different Washing Agents for Building Wastes Containing Chromium - Wang Xing-run; Zhang Yan-xia; Wang Qi; Shu Jian-min (The Scientific World Journal)
With the building wastes contaminated by chromium in Haibei Chemical Plan in China as objects, we studied the contents of total Cr and Cr (VI) of different sizes, analyzed the effect of 6 different washing agents, discussed the removal mechanisms of 6 different washing agents for Cr in various forms, and finally selected applicable washing agent. As per the results, particle size had little impact on the contents of total Cr and Cr (VI); after one washing with water, the removal rate of total Cr and Cr (VI) was 75% and 78%, respectively, and after the second washing with 6 agents, the removal rate of citric acid was the highest, above 90% for total Cr and above 99% for hexavalent chromium; the pH of building wastes were reduced by citric acid, and under acid condition, hexavalent chromium was reduced to trivalent chromium spontaneously by organic acid, which led to better removal rate of acid soluble Cr and reducible Cr; due to the complexing action, citric acid had best removal rate for oxidizable trivalent chromium. In conclusion, citric acid is the most applicable second washing agent for building wastes.